2021
DOI: 10.1039/d1fo00857a
|View full text |Cite
|
Sign up to set email alerts
|

Pediococcus pentosaceus PP04 improves high-fat diet-induced liver injury by the modulation of gut inflammation and intestinal microbiota in C57BL/6N mice

Abstract: In this study, Pediococcus pentococcus PP04 (PP04) isolated from the Northeast pickled cabbage was given to C57BL/6N mice for eight weeks, which aimed to investigate the ameliorative effects of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 48 publications
5
24
0
Order By: Relevance
“…RNA extraction and gene expression were performed as described in a previous study with minor modifications. 35,36 Briefly, the total RNA of the pancreatic tissue was extracted using a trizol reagent and the reverse transcription was performed via a first strand cDNA synthesis kit. Real-time polymerase chain reaction (RT-PCR) was conducted using SYBR FAST qPCR kit master mix universal from Kapa Biosystems according to the manufacturer's instructions, and the primer sequences are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction and gene expression were performed as described in a previous study with minor modifications. 35,36 Briefly, the total RNA of the pancreatic tissue was extracted using a trizol reagent and the reverse transcription was performed via a first strand cDNA synthesis kit. Real-time polymerase chain reaction (RT-PCR) was conducted using SYBR FAST qPCR kit master mix universal from Kapa Biosystems according to the manufacturer's instructions, and the primer sequences are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have confirmed that patients with liver disease have different degrees of gut microbiota disorder, and inflammatory factors and immune cells are involved in a variety of physiological and pathological processes in the liver, which are closely related to the occurrence and development of liver disease 9–11 . Lu et al 12 detected the main gut microbiota of healthy people, asymptomatic hepatitis B virus carriers, and patients with chronic hepatitis B by 16S ribosomal ribonucleic acid (rRNA) gene sequencing technology, and found that with disease progression, the ratio of Bifidobacteriaceae and Enterobacteriaceae in the intestine gradually decreased.…”
Section: Introductionmentioning
confidence: 99%
“…A low abundance of gut microbiota is associated with lower efficiency in improving the inflammatory response ( 23 ). Changes in gut microbiota, loss of bacterial diversity, and changes in microbial composition have been shown to be closely associated with inflammation and oxidative stress and can be remodelled through interactions between gut microbes and dietary components ( 55 ). Many studies have shown that an HFD can reduce the richness and diversity of microbial communities and change their structure.…”
Section: Discussionmentioning
confidence: 99%